Affective and attentional states when running in a virtual reality environment - Neumann, D. L.; Moffitt, R. L. (Sports, 2018)
Engaging in physical exercise in a virtual reality (VR) environment has been reported to improve physical effort and affective states. However, these conclusions might be influenced by experimental design factors, such as comparing VR environments against a non-VR environment without actively controlling for the presence of visual input in non-VR conditions. The present study addressed this issue to examine affective and attentional states in a virtual running task. Participants (n = 40), completed a 21 min run on a treadmill at 70% of Vmax. One group of participants ran in a computer-generated VR environment that included other virtual runners while another group ran while viewing neutral images. Participants in both conditions showed a pattern of reduced positive affect and increased tension during the run with a return to high positive affect after the run. In the VR condition, higher levels of immersive tendencies and attention/absorption in the virtual environment were associated with more positive affect after the run. In addition, participants in the VR condition focused attention more on external task-relevant stimuli and less to internal states than participants in the neutral images condition. However, the neutral images condition produced less negative affect and more enjoyment after the run than the VR condition. The finding suggest that the effects of exercising in a VR environment will depend on individual difference factors (e.g., attention/absorption in the virtual world) but it may not always be better than distracting attention away from exercise-related cues